Urban Environments Promote Adaptation to Multiple Stressors - Elizabeta Briski; Louisa Langrehr; Syrmalenia G. Kotronaki; Alena Sidow; Cindy Giselle Martinez Reyes; Antonios Geropoulos; Gregor Steffen; Nora Theurich; James W. E. Dickey; Jasmin C. Hütt; Phillip J. Haubrock; Ismael Soto; et al. (Ecology Letters, 2025)
Anthropogenic activities have drastically changed environmental conditions worldwide, negatively impacting biodiversity and ecosystem services. At the same time, the majority of the human population lives in urban areas that are greatly altered from natural habitats. Nevertheless, many species thrive in these urban environments. To improve our knowledge of evolution and adaptation in these anthropogenically impacted habitats, we conducted the widest series of stress experiments to date with three marine taxa: one mussel and two gammarid species. We compared intraspecific populations from protected and human‐altered habitats to determine their tolerance to salinity, temperature and partial pressure of CO 2 in water (pCO 2 ) regimes. Populations from impacted habitats typically outperformed protected habitat populations, with individuals from the most impacted habitat being the most robust. We propose that urban populations are adapting to life in disturbed environments—this adaptation concurrently promotes more resilient rescue populations but potentially confers increased invasion risk from non‐native species.